2015
DOI: 10.1680/coma.14.00047
|View full text |Cite
|
Sign up to set email alerts
|

Ambient vibration tests of a cross-laminated timber building

Abstract: Cross-laminated timber has, in the last 6 years, been used for the first time to form shear walls and cores in multi-storey buildings of seven storeys or more. Such buildings can have low mass in comparison to conventional structural forms. This low mass means that, as cross-laminated timber is used for taller buildings still, their dynamic movement under wind load is likely to be a key design parameter. An understanding of dynamic lateral stiffness and damping, which has so far been insufficiently researched,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 19 publications
1
19
0
1
Order By: Relevance
“…The exception observed in the longitudinal direction of building B5 is due to the fact that this building has concrete suspended slabs (added mass) up to the second level and concrete retaining walls at ground level. Similar observations have been made in the literature by Reynolds et al (2014), where an increase was observed in the fundamental period due to predominant increase in mass over the increase in stiffness. The increase in stiffness for finished buildings is significant because it is common practice for structural engineers to neglect the stiffness effect of non-structural components such as partition walls, external walls, parapet walls, stair walls, elevator shaft, etc but take their mass into account.…”
Section: Observation On Measured Periods and Comparison To Literaturesupporting
confidence: 91%
“…The exception observed in the longitudinal direction of building B5 is due to the fact that this building has concrete suspended slabs (added mass) up to the second level and concrete retaining walls at ground level. Similar observations have been made in the literature by Reynolds et al (2014), where an increase was observed in the fundamental period due to predominant increase in mass over the increase in stiffness. The increase in stiffness for finished buildings is significant because it is common practice for structural engineers to neglect the stiffness effect of non-structural components such as partition walls, external walls, parapet walls, stair walls, elevator shaft, etc but take their mass into account.…”
Section: Observation On Measured Periods and Comparison To Literaturesupporting
confidence: 91%
“…They tested the building under both ambient vibration and using a rotational shaker. Ambient vibration tests have also been carried out on a seven-storey CLT building (Reynolds et al, 2015). Aside from these studies, however, the majority of research into the dynamic response of such structures has been under the irreversible deformations associated with seismic loading.…”
Section: Introductionmentioning
confidence: 99%
“…The building, known as "Albina Yard, " is an example of a hybrid structure, exhibiting a mass timber gravity system, while its lateral force resisting system consists of light-frame shear walls. While extensive research has gone into characterizing the structural properties of mass timber members and subsystems, few research studies have analyzed the dynamic behavior of buildings encompassing mass timber structural products, and specifically CLT (Reynolds et al, 2014(Reynolds et al, , 2015(Reynolds et al, , 2016Hu et al, 2016). The limited number of currently built mass timber buildings, especially in North America, makes this endeavor more challenging, while it provides motivation for characterizing the as-built modal properties of this type of structures.…”
Section: Introductionmentioning
confidence: 99%